2004
DOI: 10.4314/wsa.v29i4.5056
|View full text |Cite
|
Sign up to set email alerts
|

Riverine macroinvertebrate responses to chlorine and chlorinated sewage effluents - acute chlorine tolerances of <i>Baetis harrisoni</i> (Ephemeroptera) from two rivers in KwaZulu-Natal, South Africa

Abstract: Chlorine is widely used in South African sewage treatment works, and despite its volatility is likely to have a considerable impact on riverine ecosystems. This paper considers the results of acute (96 h) toxicity responses to chlorine of riverine mayfly nymphs Baetis harrisoni collected from the small, relatively uncontaminated suburban Westville Stream, KwaZulu-Natal and from the more severely impacted Umbilo River, which flows through the industrial area of Pinetown, KwaZulu-Natal, South Africa. The 96 h LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…As mentioned above, the sensitivities of BFI measurement to SC BF and SC RO were calculated and the uncertainties of CMB results obtained using different parameter determination methods and monitoring durations were evaluated to identify the most accurate parameter calculation method and the shortest appropriate monitoring period. The dimensionless sensitivity index of BFI (output) with SC BF (uncertain input) and SC RO , S(BFI|SC BF ) and S(BFI|SC RO ), reflecting the proportional relationship between the relative error in BFI and the relative error in parameters, were calculated using the following equations (Yang et al, 2019):…”
Section: Quantitative Estimates Of the Sensitivity And Uncertainty Inmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the sensitivities of BFI measurement to SC BF and SC RO were calculated and the uncertainties of CMB results obtained using different parameter determination methods and monitoring durations were evaluated to identify the most accurate parameter calculation method and the shortest appropriate monitoring period. The dimensionless sensitivity index of BFI (output) with SC BF (uncertain input) and SC RO , S(BFI|SC BF ) and S(BFI|SC RO ), reflecting the proportional relationship between the relative error in BFI and the relative error in parameters, were calculated using the following equations (Yang et al, 2019):…”
Section: Quantitative Estimates Of the Sensitivity And Uncertainty Inmentioning
confidence: 99%
“…The average uncertainty in multiple calculation processes is then used to estimate the uncertainty in the baseflow index (BFI, long-term ratio of baseflow to total streamflow), which can be expressed as W BFI-Genereux (Genereux and Hooper, 1998;Miller et al, 2014). On the other hand, Yang et al (2019) found that random measurement errors in y k or SC k for time series exceeding 365 d will cancel each other out, allowing the influence on BFI to be ignored. An additional uncertainty estimation method of BFI can then be derived on the basis of the sensitivity analysis (Yang et al, 2019):…”
Section: Quantitative Estimates Of the Sensitivity And Uncertainty Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al (2000) found that 50% mortality (LC50) in the population of Daphnia magna was caused by 0.017 mg/L exposure to inorganic chloramines over 48 hours. Another study by Williams et al (2003) showed that benthic macro invertebrate community structure (abundance and number of taxa) substantially decreased (sometimes to zero) in river sites exposed to chlorinated sewage.…”
Section: Free Chlorine (Cl2)mentioning
confidence: 99%
“…Zokufa et al (2001) showed that groundwater from these pastures still reaches the river via springs and is the main contributing factor to the salinisation problem. The effect of salts on the river's aquatic biota, and in particular macroinvertebrates, has been the topic of a number of laboratory and field-based toxicity studies (Palmer et al 1996, Zokufa et al 2001, Williams et al 2003, Kefford et al 2004. Nevertheless, the extent to which salinisation influences macroinvertebrate community structure in the Elands is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%